Improvement of ship berthing operation at port container terminal via discrete event simulation - Shahpanah, Ataollah (2014)
Port container terminal play the leading role in transition goods and products between continents. Competition in the port industry increase dramatically, for this reason most of the port management tries to enhance their service rate and productivity to get competitive advantages. For enhancing the productivity rate of port container terminal management tries to solving queue problem at port terminal in order to decrease ships waiting time and ships turnaround time. This study try to enhance port terminal productivity rate and reduced ships waiting time at berthing area of port container terminal. The data was collected from berthing area of PCT port container terminal located at Southern Malaysia as case study, and based on these data the simulation model was built with using Arena 13.5 software. After verification and validation model, different scenarios were tested to improvement ships berthing operation at PCT port container terminal. Three kind of scenarios were tested; first category of scenarios focused on the ships waiting time and try to reduced ships waiting time without any reduction on productivity rate, second type of scenarios are based on the PCT afford and last type of scenarios tried to enhanced port resource and equipments to optimize the productivity rate and ships waiting time. After tested around 80 alternatives on these categories the best productivity rate at each categories were selected and for choosing proper alternatives waiting time was considered. That means the alternatives which have high productivity rate and low waiting times were selected to improved ships operation at PCT port container terminal